An unusual presentation of a ruptured degenerative fibroid in a perimenopausal woman. (9th December 2014) - Seet, Meei Jiun; Chonkar, Sonali; Mathur, Manisha
Abstract : A 55-year-old woman in a perimenopausal state presented with severe suprapubic pain and fever. Physical examination revealed a tender pelvic mass measuring 24 weeks in size. Ultrasound of the pelvis and CT scan of the abdomen and pelvis showed a 12 cm mass arising from the posterior wall of the uterus with irregular margin inferiorly, raising suspicion of a ruptured mass. The patient was treated conservatively and discharged from the hospital with regular simple analgaesia. She had an elective total hysterectomy bilateral salpingo-oophrectomy and frozen section the following week and histology revealed a benign leiomyoma with extensive necrosis. Moreover, intraoperatively, the fibroid was found to have ruptured its capsule. This case illustrates that a ruptured degeneration of uterine leiomyoma should be considered as one of the differential diagnoses for all women presenting with abdominal pain and a large fibroid mass regardless of their hormonal status or age.